The specialist pharmacist and quality indicators of medication use in the care of people with intellectual disabilities and behaviour disorders - Flood, Bernadette (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2016)
Quality Medication Use and the Population with Intellectual Disabilities and Behaviour Disorders. A Modified Delphi Technique to develop Quality Indicators and a Grounded Theory approach to information provided by people with Intellectual Disabilities. In healthcare, the process of medication use is a means to produce value for the patient with intellectual disability and to maintain or improve their health. This process is of varying quality in the vulnerable population with intellectual disabilities and behaviour disorders. To address the evident health inequities in this population the medication use process should be made predictable with only chance causes of variation left in the process. Quality Indicators (QIs) are explicitly defined and measurable items referring to the structures, processes or outcomes of care that infer a judgement about the quality of care provided. This thesis describes a two part project that aimed to improve the quality of the medication use process for people with intellectual disabilities and behaviour disorders. Two separate applications were made to the university research ethics committee for approval to undertake each part of the project. The Delphi process has been widely used for QI development in healthcare. Part 1 of this project involved a Modified Delphi Technique (MDT); a structured process involving a series of questionnaires or ‘rounds’ to gather information. Candidate Qls were developed using narrative literature and guideline review and expert evaluation. The candidate Qls were submitted to a 32-member panel of multidisciplinary experts, from Ireland and the UK. The MDT panel included psychiatrists, pharmacists, nursing personnel, speech and language therapists, geriatricians, psychologists and representation from academia, regulation and administration. Over two rounds the Qis were rated for importance, scientific soundness and feasibility on a 9 point Likert scale. Consensus criteria were preset. Participants were chosen based on their willingness to participate and knowledge of the population with intellectual disabilities. A total of 38 candidate QIs underwent Delphi scoring. QIs addressed patient experience, access to care, continuity of care, equity, patient safety, effectiveness, appropriateness and assessment. Following round one, 23 QIs were accepted, none were rejected and 15 were equivocal. A total of 30 candidate QIs were accepted following round two. Selection criteria were raised to differentiate the hierarchy of the final list. The following six crucial QIs were identified, rated by 90% or more of the panel as important: Medication Review, General Health Review, Restrictive Practice, Excessive Dose Anti- Psychotics, Gradual Dose Reduction and Dementia Anti-Psychotic Medication. The experience of all patients in healthcare is an accepted arm of quality. Patients say that they care about their experience of care as much as clinical effectiveness and safety. Six people with intellectual disabilities were interviewed in Part 2. The aims of this qualitative study, using Grounded Theory were to discover how informed the participants with intellectual disabilities are about their medication and to identify key factors relating to their experiences and understanding of the medication use process. Grounded Theory highlights the importance of developing an understanding of human behaviour through a process of discovery and induction. It aims to enquire and state how participants interpret reality and is attentive to how theory emerges from the subjective experiences of the participants. Six people with intellectual disabilities supported by a national voluntary support organisation consented to participate. Pat, a diabetic, was identified as the index case in the analysis and his situation is analysed in detail in the thesis document. The main theory developed in Part 2 of this project is that there is a role and need for ‘specialist pharmacists’ in the healthcare of vulnerable people with intellectual disabilities. A significant sub theory was that ‘self determination’ by the person with intellectual disabilities in the medication use process poses difficulties and may not ensure the highest quality care. Quality of care can be defined as "the degree to which health services for individuals and populations increase the likelihood of desired health outcomes and are consistent with current professional knowledge". The medication use process in this population is of vital importance as it will have an impact on the health status of the population and on healthcare costs. Pharmacists and others can only be sure to improve what they can actually measure and quality cannot be measured without QIs. QIs developed in the project have a potential impact on health, they are meaningful and susceptible to being influenced by the health system and/or a pharmacist or other health professional. The implicit notion in selecting the QIs in this project is that there is a significant quality gap in the medication use process in this vulnerable population group that needs to be addressed. This project was the first attempt to develop QIs for the medication use process in people with intellectual disabilities and behaviour disorders. They infer a judgement about the quality of care provided in the medication use process. They are important definitions of quality care for people with intellectual disabilities and behaviour disorders and will support ‘specialist pharmacists’ and others involved in quality improvement in the medication use process in this vulnerable population.
Keywords: Pharmacy & Phamaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin